Participation of the arcRACME protein in self-activation of the arc operon located in the arginine catabolism mobile element in pandemic clone USA300 (2017)
Staphylococcus aureus pandemic clone USA300 has, in addition to its constitutive arginine catabolism (arc) gene cluster, an arginine catabolism mobile element (ACME) carrying another such cluster, which gives this clone advantages in colonisation and infection. Gene arcR, which encodes an oxygen-sensitive transcriptional regulator, is inside ACME and downstream of the constitutive arc gene cluster, and this situation may have an impact on its activation. Different relative expression behaviours are proven here for arcRACME and the arcACME operon compared to the constitutive ones. We also show that the artificially expressed recombinant ArcRACME protein binds to the promoter region of the arcACME operon; this mechanism can be related to a positive feedback model, which may be responsible for increased anaerobic survival of the USA300 clone during infection-related processes.